2019
DOI: 10.1371/journal.pone.0225219
|View full text |Cite
|
Sign up to set email alerts
|

Malaria screening at the workplace in Cameroon

Abstract: Malaria remains a major health problem in Cameroon; It accounts for 38% of consultations, 24% of deaths and 36.8% of absenteeism in the country. The negative economic impact of malaria has encouraged a new control approach targeting companies. In this regard, a cross sectional study was conducted from February 2015 to June 2017 in 14 companies in the town of Douala. This study aimed at determining the prevalence, control practices of employees and identifying associated factors with malaria. A total of 2705 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
3
21
3
1
Order By: Relevance
“…Children under ve years are more vulnerable to the disease in areas of high transmission [41] and it is often associated to the poorly developed immune system in this age group [42]. Observations from this study did not report any association between gender and Plasmodium infection, consistent with studies by Kwenti et al [43] and Mbohou et al [44] in other parts of the country.…”
Section: Malaria Parasite Itn Knowledge and Haematological Indicessupporting
confidence: 88%
“…Children under ve years are more vulnerable to the disease in areas of high transmission [41] and it is often associated to the poorly developed immune system in this age group [42]. Observations from this study did not report any association between gender and Plasmodium infection, consistent with studies by Kwenti et al [43] and Mbohou et al [44] in other parts of the country.…”
Section: Malaria Parasite Itn Knowledge and Haematological Indicessupporting
confidence: 88%
“…A recent study on malaria in some enterprises in Cameroon revealed 30.1% prevalence of the infection among employees [ 11 ]. Given the magnitude of the disease and its potential negative impact on businesses [ 12 ], enterprises should better commit in malaria prevention and control [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has some drawbacks limiting its optimal utilization in African settings. These include mainly the need for skilled microscopist, good quality reagents and microscope, and electricity which is often lacking in resource-limited and difficult-to-reach areas [17,21,45,52]. In addition, the method is particularly time consuming which is not allow for prompt management of malaria cases.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is part of a larger study on malaria carried out in some companies in the town of Douala, Littoral Region, Cameroon. The conditions and characteristics of the study site have been described elsewhere [21]. Briefly, Douala represents the economic capital with 35.1% of companies of Cameroon.…”
Section: Study Sites and Populationmentioning
confidence: 99%
See 1 more Smart Citation